Gold Nanoparticles for Brain Tumor Imaging: A Systematic Review - Meola, Antonio; Rao, Jianghong; Chaudhary, Navjot; Sharma, Mayur; Chang, Steven D. (Frontiers in Neurology, 2018)
Abstract Background: Demarcation of malignant brain tumor boundaries is critical to achieve complete resection and to improve patient survival. Contrast-enhanced brain magnetic resonance imaging (MRI) is the gold standard for diagnosis and pre-surgical planning, despite limitations of gadolinium (Gd)-based contrast agents to depict tumor margins. Recently, solid metal-based nanoparticles (NPs) have shown potential as diagnostic probes for brain tumors. Gold nanoparticles (GNPs) emerged among those, because of their unique physical and chemical properties and biocompatibility. The aim of the present study is to review the application of GNPs for in vitro and in vivo brain tumor diagnosis. Methods: We performed a PubMed search of reports exploring the application of GNPs in the diagnosis of brain tumors in biological models including cells, animals, primates, and humans. The search words were “gold” AND “nanoparticle” AND “brain tumor”. Two reviewers performed eligibility assessment independently in an unblinded standardized manner. The following data were extracted from each paper: first author, year of publication, animal/cellular model, GNP geometry, GNP size, GNP coating (i.e. PEG, gadolinium), blood-brain barrier (BBB) crossing aids, imaging modalities, and therapeutic agents conjugated to the GNPs, Results: The PubMed search provided 100 items. A total of 16 studies, published between the 2011 and 2017, were included in our review. No studies on humans were found. Thirteen studies were conducted in vivo on rodent models. The most common shape was a nanosphere (twelve studies). The size of GNPs ranged between 20 nm and 120 nm. In eight studies, the GNPs were covered in polyethylene glycol (PEG). The BBB penetration was increased by surface molecules (nine studies) or by means of external energy sources (in two studies). The most commonly used imaging modalities were MRI (four studies), surface-enhanced Raman scattering (SERS) (three studies), and fluorescent microscopy (three studies). In two studies, the GNPs were conjugated with therapeutic agents. Conclusion: Experimental studies demonstrated that GNPs might be versatile, persistent and safe contrast agents for multimodality imaging, thus enhancing the tumor edges pre-, intra- and post-operatively improving microscopic precision. The diagnostic GNPs might also be used for multiple therapeutic approaches, namely as “theranostic” NPs.